La escenografía teatral y los sistemas de producción - Vera, Alicia Beatriz (2016)
The importance of giving quality to the construction process and stage production lies in the responsibility of the overall image of the staging, the management and supervision of the effectiveness and safety of the designed scenic devices, habitat of representation. The scenographic production is an elaboration process in which the following issues stand out: Concept, Project Design - Materialization, Construction- Execution, Assemblage-Circulation. The project proposes to investigate, review and analyze stage design holistically. Three stages were determined: pre-production, production and representation, meaning the relationship between productive stages and their outcome. The above presents a perceived difficulty in the professional area: the relationship between design, production process and stage product. Once identified and defined, emerges as an object of study. We will select already premiered plays and shows, significant for its renewal, innovation or for generate creative proposals with limitated production conditions. The project will diagnose a key subject. It is planned to evaluate and propose specific instruments to get into a greater consistency in it. The results will have significant relevance for the University classes, the art world and society in general.